The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.46743/2160-3715/2018.3280
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Positive Outcomes of Decision Making Biases in the Field of Entrepreneurial Marketing

Abstract: Entrepreneurs make important decisions regarding different aspects of their enterprises. Given the bulk of uncertainty, complexity as well as the rapid rate of change in their business environment, entrepreneurs’ decisions, including their marketing decisions, are prone to decision-making biases. Previous research has mainly focused on the negative outcomes of decision-making biases for entrepreneurs. We argue that sometimes entrepreneurial decision-making biases could have positive outcomes, too. Ignoring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, before such benefits have been realised, entrepreneurs must have learnt to cope with failure they would have gone through. Whilst failure could affect the ability to learn critical lessons from the incidents, Shepherd (2003) has proposed that failure arising from entrepreneurial strategic decision-making, if well managed, can become a relevant learning curve and an important source of wisdom and entrepreneurial education for entrepreneurs (Kuntze & Matulich 2016;Nouri et al 2018), especially as they may want to embark on a business rescue mission (le Roux & Pretorius 2017), where learning from the failure would prove worthwhile. Other scholars such as Cannon and Edmondson (2005) have noted that benefits of failure are more in providing counselling and encouragement than they are in pragmatic situations; it is therefore important to comprehend the environment and circumstances in which failure has occurred in order to make the best out of the situation.…”
Section: Entrepreneurial Failure: Performance Nexusmentioning
confidence: 99%
“…However, before such benefits have been realised, entrepreneurs must have learnt to cope with failure they would have gone through. Whilst failure could affect the ability to learn critical lessons from the incidents, Shepherd (2003) has proposed that failure arising from entrepreneurial strategic decision-making, if well managed, can become a relevant learning curve and an important source of wisdom and entrepreneurial education for entrepreneurs (Kuntze & Matulich 2016;Nouri et al 2018), especially as they may want to embark on a business rescue mission (le Roux & Pretorius 2017), where learning from the failure would prove worthwhile. Other scholars such as Cannon and Edmondson (2005) have noted that benefits of failure are more in providing counselling and encouragement than they are in pragmatic situations; it is therefore important to comprehend the environment and circumstances in which failure has occurred in order to make the best out of the situation.…”
Section: Entrepreneurial Failure: Performance Nexusmentioning
confidence: 99%
“…Busenitz (1999) argues that in the uncertain environment of business start-ups, many new ventures wouldn't exist without the use of biases. Nouri et al (2018) conclude that biases could have certain positive outcomes such as survival in the market, overcoming rivalry, as well as innovative behavior. And finally, Zhang et al (2020) suggest that certain levels of biases may enhance entrepreneurs' performance.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…On the other hand, regarding heuristics, the study of Sinyard et al (2020) agree that heuristics and entrepreneurship with the evidence of entrepreneurial action are related. Likewise, Nouri et al (2018) observed that heuristic influence entrepreneurial behaviour while it also supported entrepreneurs in making decisions despite limited resources.…”
Section: The Key Findingsmentioning
confidence: 97%